When in French : love in a second language - Collins, Lauren. (Journalist) (London : 4th Estate, 2016)
"A language barrier is no match for love. Lauren Collins discovered this firsthand when, in her early thirties, she moved to London and fell for a Frenchman named Olivier--a surprising turn of events for someone who didn't have a passport until she was in college. But what does it mean to love someone in a second language? Collins wonders, as her relationship with Olivier continues to grow entirely in English. Are there things she doesn't understand about Olivier, having never spoken to him in his native tongue? Does "I love you" even mean the same thing as "je t'aime"? When the couple, newly married, relocates to Francophone Geneva, Collins--fearful of one day becoming "a Borat of a mother" who doesn't understand her own kids--decides to answer her questions for herself by learning French. When in Frenchis a laugh-out-loud funny and surprising memoir about the lengths we go to for love, as well as an exploration across culture and history into how we learn languages--and what they say about who we are. Collins grapples with the complexities of the French language, enduring excruciating role-playing games with her classmates at a Swiss language school and accidently telling her mother-in-law that she's given birth to a coffee machine. In learning French, Collins must wrestle with the very nature of French identity and society--which, it turns out, is a far cry from life back home in North Carolina. Plumbing the mysterious depths of humanity's many forms of language, Collins describes with great style and wicked humor the frustrations, embarrassments, surprises, and, finally, joys of learning--and living in--French"--
"When New Yorker staff writer Lauren Collins moves to Geneva, Switzerland, she decides to learn French--not just to be able to go about her day-to-day life, but in order to be closer to her French husband and his family. When in French is at once a hilarious and idiosyncratic memoir about the things we do for love, and an exploration across cultures and history into how we learn languages, and what they say about who we are"--
Keywords: Collins, Lauren -- (Journalist); Journalists -- United States -- Biography; Travelers' writings, American -- France; French language -- Conversations and phrases -- English; French language -- Self-instruction.; French language -- Study and teaching -- English speakers; BIOGRAPHY & AUTOBIOGRAPHY / Literary; TRAVEL / Europe / France; HUMOR / Topic / Marriage & Family; France -- Languages